Perceptions of Clinical Academics and People With Parkinson's Disease on Delivery of Regional Interdisciplinary Model of Care: Qualitative Descriptive Study - Sue Sharrad; Joanne Harmon (SAGE Publishing, 2024)
Introduction/Objective: The objective of the study was to develop an understanding of the perceptions of people with Parkinson's disease and clinical academics on the implementation of a regional interdisciplinary model of care. Methods: A qualitative descriptive study was undertaken. A PD interdisciplinary clinic was conducted in an Australian regional location. As a novel variation, in this clinic, 4 clinical academics consulted simultaneously offering a long, 3-h appointment. Following the clinic, we conducted 2 focus groups with all clinical academics and 6 semi-structured interviews with people with PD and carers. Data were analyzed using Elo & Kyngäs' inductive content analysis approach. Results: An overarching main category namely, "interdisciplinary care proved valuable to regional people with PD and clinical academics," and 3 generic-categories including "identifying interdisciplinary care as a viable option in regional locations," "current care provision is disempowering and burdensome," and "regional residing people with PD and their carers seek locally accessible healthcare with PD skilled clinicians" were identified. Conclusion: Our findings suggest the implementation of interdisciplinary care to regional healthcare systems is valued by clinical academics and people with PD and carers. Further research is required to establish how interdisciplinary care can be implemented in regional Australia and its effects on practice changes, patient outcomes, and quality of life.